Maternal age, birth order, and race: differential effects on birthweight - Swamy, Geeta K (2010)
BACKGROUND: Studies examining the influence of maternal age and birth order on birthweight have not effectively disentangled the relative contributions of each factor to birthweight, especially as they may differ by race. METHODS: A population-based, cross-sectional study of North Carolina births from 1999 to 2003 was performed. Analysis was restricted to 510 288 singleton births from 28 to 42 weeks’ gestation with no congenital anomalies. Multivariable linear regression was used to model maternal age and birth order on birthweight, adjusting for infant sex, education, marital status, tobacco use and race. RESULTS: Mean birthweight was lower for non-Hispanic black individuals (NHB, 3166 g) compared with non-Hispanic white individuals (NHW, 3409 g) and Hispanic individuals (3348 g). Controlling for covariates, birthweight increased with maternal age until the early 30s. Race-specific modelling showed that the upper extremes of maternal age had a significant depressive effect on birthweight for NHW and NHB (35+ years, p<0.001), but only age less than 25 years was a significant contributor to lower birthweights for Hispanic individuals, p<0.0001. Among all racial subgroups, birth order had a greater influence on birthweight than maternal age, with the largest incremental increase from first to second births. Among NHB, birth order accounted for a smaller increment in birthweight than for NHW and Hispanic women. CONCLUSION: Birth order exerts a greater influence on birthweight than maternal age, with signficantly different effects across racial subgroups.